2013
DOI: 10.3848/iif.2013.328.3749
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Bank Lending Channel in Turkey

Abstract: This paper is based on Ekin Ayşe Özşuca's PhD thesis prepared under the supervision of Elif Akbostancı at the Department of Economics, METU. Ekin Ayşe Özşuca would like to thank to Erdal Özmen, Fatih Özatay, Gül İpek Tunç, Teoman Pamukçu, Yener Altunbaş and Yunus Aksoy for helpful comments on her PhD thesis. This research was supported by TUBITAK 2214-coded Ph. D. scholarship program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Most of the studies on advanced economies have found the importance of the credit channel (Garretsen & Swank, 1998 Leroy, 2014). However, there is some evidence that suggests the partial presence or absence of the credit channel (Ramey, 1993;Çavuşoğlu, 2002;Garretsen & Swank, 2003;Suzuki, 2004;Ozsuca & Akbostanci, 2012). The evidence on emerging market economies (EMEs) is inconclusive about the effectiveness of the credit channel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the studies on advanced economies have found the importance of the credit channel (Garretsen & Swank, 1998 Leroy, 2014). However, there is some evidence that suggests the partial presence or absence of the credit channel (Ramey, 1993;Çavuşoğlu, 2002;Garretsen & Swank, 2003;Suzuki, 2004;Ozsuca & Akbostanci, 2012). The evidence on emerging market economies (EMEs) is inconclusive about the effectiveness of the credit channel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results display the limited impact of monetary shocks on loan supply, especially in the post-inflation targeting era. Özşuca and Akbostancı (2013) investigated the effect of monetary policy on credit growth between 1988 and 2009. The empirical analysis builds on cross-sectional heterogeneity in banks' lending supply responses using the size and CAMEL-type variables to appeal to a bank's financial health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, significant coefficients emerge for only earnings capability and asset quality in banks' response to monetary policy changes for the period before the 2001 crisis. Notably, our study is methodologically in the spirit of Özşuca and Akbostancı (2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the effects of the monetary tightening are more negative for smaller, less liquid and less capitalized banks. Ozsuca and Akbostanci (2012) found the existence of the bank lending channel in the case of Turkey with the significant distributional effects due to the bank specific characteristics in the impact of monetary policy on the supply of bank loans. Size and capitalization of the banks are found to be important determinant of the loan supply in Estonia (Juks, 2004), Jamica (Urquhart, 2006) and Jordan (Boughrara and Ghazouni, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%